THE EFFECT OF CHLORELLA sp SPEAT FLOUR FORTIFICATION ON MAKING SEAWEED JAM (Euchemacottoni) - Ezi Melia Rahmi; Syahrul Syahrul; Dewita Buchari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            This study aimed to determine the effect of fortification Chlorella sp flour on the manufacture of seaweed jam.The experimental method was conducted by experimental method by making seaweed jam with fortified Chlorellasp flour ie without addition of Chlorella sp flour with 4 level of treatment that is addition of 1 gr of Chlorella flour, addition of 2 gr of Chlorella flour, addition of 3 gr of Chlorella flour. The results showed that fortification of Chlorella sp flour in the best seaweed jam was the addition of Chlorella sp 1gr flour with the value of rupa as much as 78 panelists (97,50%), with the criteria of young green appearance. The scent of 78 panelists (97.50%) with the criteria of the smell of Chlorella began to smell. Tektur as much as 79 panelists (98.75%) with thick texture criteria. The taste of 77 panelists (96.25%) with Chlorella taste criteria slightly felt. With moisture content 33.38%, reducing sugar content 57.02% and protein content 6.07%.Keywords: seaweed, Chlorella sp flour